1997
DOI: 10.1002/pro.5560060511
|View full text |Cite
|
Sign up to set email alerts
|

Hsc66 and Hsc20, a new heat shock cognate molecular chaperone system from Escherichia coli

Abstract: The hscA and hscB genes of Escherichia coli encode novel chaperone and co-chaperone proteins, designated Hsc66 and Hsc20, respectively. We have overproduced and purified Hsc66 and Hsc2O in high yield in E. coli and describe their initial characterization including absorbance, fluorescence, and circular dichroism spectra. Immunoblot analyses of E. coli cultures using antisera to Hsc66 and Hsc20 raised in rabbits establish that Hsc66 and Hsc2O are constitutively expressed at levels corresponding to cell concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
116
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 56 publications
3
116
0
1
Order By: Relevance
“…Overexpression and Purification of Proteins-Recombinant Hsc66, Hsc20, and IscU were prepared as previously described (2,10). In addition, purified Hsc20 was treated to remove any contaminating IscU by affinity chromatography using IscU antiserum coupled to CNBractivated Sepharose.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overexpression and Purification of Proteins-Recombinant Hsc66, Hsc20, and IscU were prepared as previously described (2,10). In addition, purified Hsc20 was treated to remove any contaminating IscU by affinity chromatography using IscU antiserum coupled to CNBractivated Sepharose.…”
Section: Methodsmentioning
confidence: 99%
“…ATPase Assays-Steady-state ATPase rates were determined at 23°C in HKM buffer (50 mM Hepes, pH 7.3, 150 mM KCl, 10 mM MgCl 2 ) containing 1 mM DTT and 0.5 mM ATP by measuring phosphate released using the EnzCheck coupled enzyme phosphate assay kit (20) (Molecular Probes) as previously reported (2,3,10,13,14,21). Under these conditions Hsc66 has a basal turnover number of Х0.10 min Ϫ1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hscB gene in bacteria encodes a 20-kDa J-type co-chaperone, designated Hsc20, that functions with the hsp70-class molecular chaperone HscA/Hsc66 (Seaton and Vickery 1994;Kawula and Lelivelt 1994;Vickery et al 1997). In vitro studies have shown that HscB/Hsc20 regulates interactions between the Fe-S cluster assembly protein IscU and the HscA/ Hsc66 chaperone (Hoff et al 2000;Silberg et al 2001;Hoff et al 2002).…”
Section: Introductionmentioning
confidence: 99%